THE ACQUISITION OF SWEAR WORDS BY STUDENTS IN CENTRAL KALIMANTAN - Friyanto Friyanto; Ashadi Ashadi (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
Swear words are often associated to inappropriate expressions in all societies. This study investigates the acquisition of swear words by Indonesian students using social media which was designed in descriptive qualitative approach. Data were gathered by questionnaireand interviews method. Result shows that the students tend to use animal terms to swear  to show anger to others. Further, friendship becomes the main source of their acquisition of swear words and these students tend to swear among themselves to show intimacy. Moreover, these students admitted that they learnt how to swear from social media and free videos available on-line.